DEVELOPMENT OF DIDACTIC COMPETENCE OF STUDENTS ON THE BASIS OF AN INTEGRATIVE APPROACH - Firyuza Orazovna Orazova (European Science Publishing, 2024)
This article describes the fact that the formation of basic life competencies is an actual socio-pedagogical problem, the concepts of "competence", "competence", their structure, various approaches to these concepts, the role of competence and competence in personal development. The approaches of many pedagogues and psychologists have been analyzed. As a result of these analyses, scientific opinions are stated. Accordingly, this article serves as a program for pedagogic scientists, teachers, authors of programs and textbooks, and researchers.
Keywords: competence, competence, personal development, educational process, knowledge, skills, competence, basic life competence, scientific competence.